2019
DOI: 10.1007/s00221-019-05660-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of neuromuscular electrical stimulation and voluntary commands on the spinal reflex excitability of remote limb muscles

Abstract: It is well known that contracting the upper limbs can affect spinal reflexes of the lower limb muscle, via intraneuronal networks within the central nervous system. However, it remains unknown whether neuromuscular electrical stimulation (NMES), which can generate muscle contractions without central commands from the cortex, can also play a role in such inter-limb facilitation. Therefore, the objective of this study was to compare the effects of unilateral upper limb contractions using NMES and voluntary unila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 52 publications
3
19
0
1
Order By: Relevance
“…However, it must be kept in mind that BCI control requires constant modification of two adaptive controllers, i.e., the decoding system as well as the brain [ 152 ]. A recent elegant study in non-human primates, showed that BCI-controlled FES can be used to induce adaptive cortical changes throughout different sensorimotor cortical sites [ 61 ]. Specifically, through use of a BCI system, cortical activity became localized around an arbitrarily selected cortical site that was used for controlling FES of upper-limb muscles in primates.…”
Section: Brain-controlled Electrical Stimulation Of Muscles and Nervementioning
confidence: 99%
See 1 more Smart Citation
“…However, it must be kept in mind that BCI control requires constant modification of two adaptive controllers, i.e., the decoding system as well as the brain [ 152 ]. A recent elegant study in non-human primates, showed that BCI-controlled FES can be used to induce adaptive cortical changes throughout different sensorimotor cortical sites [ 61 ]. Specifically, through use of a BCI system, cortical activity became localized around an arbitrarily selected cortical site that was used for controlling FES of upper-limb muscles in primates.…”
Section: Brain-controlled Electrical Stimulation Of Muscles and Nervementioning
confidence: 99%
“…Specifically, through use of a BCI system, cortical activity became localized around an arbitrarily selected cortical site that was used for controlling FES of upper-limb muscles in primates. The targeted cortical areas, which included locations in the primary motor (M1), premotor (PM), and somatosensory (S1) cortex, could be reset and localized to a new site rapidly using BCI-FES training [ 61 ]. Although the evidence was shown in non-human primates using invasive techniques, this study provides important implications that BCI-FES system should balance adaptive control to guide neuroplasticity within specific cortical areas.…”
Section: Brain-controlled Electrical Stimulation Of Muscles and Nervementioning
confidence: 99%
“…These studies suggest that cortical disinhibition may contribute to corticospinal remote facilitation between upper-and lower-limb muscles. Moreover, H-reflex responses elicited by peripheral nerve stimulation (e.g., Jendrássik E, 1883; Kawamura & Watanabe, 1975;Borroni et al, 2005) as well as posterior-root spinal reflex responses elicited by transcutaneous spinal cord stimulation (Kato et al, 2019;Masugi et al, 2019;Sasaki et al, 2020a) in the upper-or lower-limb muscles were facilitated by remote limb muscle contractions. These studies indicate spinal reflex remote modulation mechanisms also contribute to interlimb remote facilitation.…”
Section: Possible Mechanisms Of Arm-trunk Corticospinal Remote Facilitationmentioning
confidence: 99%
“…4 Moreover, his group demonstrated that epidural spinal cord stimulation (SCS) can improve standing and walking function of individuals with Parkinson's disease. 5 In addition to stimulating muscles, Dr Milosevic also uses non-invasive brain stimulation 10 as well as transcutaneous SCS [11][12][13] to probe and activate the central nervous system. Most recently, he and his team have been using a motor imagery-based brain-computer interface to control FES, which can elicit facilitation in the central nervous system via associative Hebbian learning by activation of cortical and peripheral circuits, in addition enabling restoration of motor function.…”
mentioning
confidence: 99%